Reproductive factors and breast arterial calcification: a systematic review and meta-analysis. (4th March 2022) - Lee, S. C.; Pirikahu, S.; Phillips, M.; Bellinge, J.; Stone, J.; Wylie, E.; Stuckey, B. G. A.; Schultz, C.
Abstract: Background: Breast arterial calcification (BAC) is a common incidental finding on screening mammography. Recent evidence suggests that BAC is associated with cardiovascular disease (CVD). We systematically reviewed the associations between BAC and reproductive factors (menopausal status, hormone replacement therapy [HRT] use, oral contraceptive [OC] use and parity). Methods: MEDLINE and EMBASE databases, references of relevant papers and Web of Science were searched up to February 2020 for English-language studies that evaluated these associations. Study quality were determined and a random effects model was used to assess these associations. Results: Nineteen observational studies ( n = 47, 249; three cohort studies, seven case–control studies, nine cross-sectional studies) were included. BAC was associated with menopause (nine studies; n = 15, 870; odds ratio [OR] 2.67; 95% confidence interval [CI] 1.50–4.77) and parity (seven studies; n = 27, 728; OR 2.50; 95% CI 1.68–3.71) and inversely with HRT use (10 studies; n = 33, 156; OR 0.57; 95% CI 0.40–0.80). No association was found with OC use. Eleven studies were considered good in quality. Marked heterogeneity existed across all analyses. Conclusions: BAC is associated with HRT use, menopause and parity. However, careful interpretation is required as marked heterogeneity existed across all analyses. Traditional cardiovascular risk factors may need to be taken into account in future investigations of associations between BAC and reproductive factors. PROSPERO: CRD42020141644.